Towards Improving Welding Skills: Creating Innovative Modules For Teaching SMAW Integrated 3D Animation - Yunus, Yunus; Wibowo, Theodorus Wiyanto; Pambudi, Rizdana Galih; Prayogo, Aji Catur (Jurnal Ilmu Pendidikan, 2024)
This research aims to develop teaching modules on welding techniques in vocational schools using the problem-based learning (PBL) model, a scientific learning approach, and an authentic assessment of welding competency using the manual arc welding or SMAW welding process. The development of teaching modules at vocational schools will improve the quality of the process and the quality of learning outcomes for SMAW welding engineering subjects at vocational schools. This research uses a development research method with a research design using design-based research (DBR), which refers to the instructional design model (IDM) development model design. The participants involved in this research were class XI vocational school students in East Java. The module validity test assessment results have an average score of 3.8 in the very valid category. The SMAW welding technique module that has been prepared can be used to implement SMAW welding technique learning at vocational schools. The teaching module evaluation stage results show an outstanding category, meaning the teaching module developed meets practical requirements. All students' average normalized gain score was 0.72, included in the high improvement category. The results of observations of the implementation of the PBL model facilitated by teaching modules from two observers were analyzed using percentages of agreement (PA). The research conclusion shows that the teaching module developed is valid, practical, and effective